A kind of high temperature resistant industrial lubricating oil and preparation method thereof

By introducing high-temperature-resistant composite microcapsules and carbon nanotubes into the lubricant, the microcapsule layer is formed and the thermal conductivity is improved, which solves the problem of the failure of existing high-temperature-resistant lubricant in high-temperature environments, and significantly improves the lubricating performance and mechanical life. .

CN116855300BActive Publication Date: 2025-01-03DONGGUAN QINZHEN LUBRICATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310544037.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-15
Publication Date
2025-01-03
Estimated Expiration
2043-05-15

AI Technical Summary

Technical Problem

The existing high-temperature resistant lubricating oil fails under high temperature environments and cannot effectively protect the machinery, resulting in damage to bearings, chains, slide rails and gears.

Method used

A specially made high-temperature resistant composite microcapsules are introduced into the lubricating oil, combined with carbon nanotubes, forming a microcapsule layer to slowly release silicone oil, reducing friction coefficient and wear rate, and improving thermal conductivity through composite gels.

Benefits of technology

It significantly reduces the friction coefficient and wear rate of the mechanical metal surface, reduces heat generation, improves the high-temperature resistance of lubricating oil, extends the service life of the machinery, and remains stable under high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004229132130000111
    Figure BDA0004229132130000111
  • Figure BDA0004229132130000112
    Figure BDA0004229132130000112
  • Figure BDA0004229132130000121
    Figure BDA0004229132130000121
Patent Text Reader

Abstract

The present invention relates to the technical field of lubricating oils, and in particular to a high temperature resistant industrial lubricating oil and a preparation method thereof, comprising the following raw materials in parts by weight: 25-40 parts of hydrogenated base oil, 15-25 parts of synthetic base oil, 3-6 parts of high temperature resistant composite microcapsules, 1-2 parts of carbon nanotubes, 1-2 parts of trihydroxybenzoic acid, 0.1-0.8 parts of sulfonate, 1-5 parts of surfactant, 0.5-1.0 parts of antioxidant, and 1-2 parts of dispersant. In the present invention, by introducing special high temperature resistant composite microcapsules into the conventional components of lubricating oil, an adhesion effect can be generated on the surface of mechanical metal to form a microcapsule layer, and the silicone oil wrapped inside can be slowly released to form an effective boundary lubrication film on the surface of mechanical metal, so that the friction coefficient and wear rate of the mechanical metal surface are significantly reduced, thereby effectively reducing the generation of heat during friction and reducing the ambient temperature of mechanical metal. At the same time, in combination with carbon nanotubes, the lubricating oil has good thermal conductivity, thereby further improving high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lubricating oils, in particular to a high-temperature resistant industrial lubricating oil and a preparation method thereof. Background Art

[0002] Lubricants are liquid or semi-solid lubricants used in various types of automobiles and machinery to reduce friction and protect machinery and workpieces. They are primarily composed of a base oil and lubricant additives. The lubricity and wear resistance of lubricants are primarily determined by the lubricant additives. Applying lubricants to mechanical contact areas can enhance the wear resistance of mechanical components and reduce wear. Repeated friction can easily generate high temperatures in mechanical contact areas. If the lubricant cannot quickly transfer the heat, these contact areas can easily deform or become damaged.

[0003] For example, the invention patent with announcement number CN104498152A discloses a high-temperature resistant lubricant, including base oil, methacrylate, polyisobutylene, polytetrafluoroethylene, calcium sulfonate, sodium carboxymethyl cellulose, acrylic acid grafted starch, 1,3-propylene glycol, alkyl methacrylate and high-temperature resistant additives. The high-temperature resistance of the base oil is improved by adding high-temperature resistant additives. A mixture of boron nitride powder, polyvinyl alcohol and nano-silicon dioxide is used as a high-temperature resistant additive. It has good high-temperature resistance and works together with other additives to improve the lubrication performance of the base oil. However, the high-temperature resistance of the lubricant is limited. In some bearings, chains, slide rails and gears with an ambient temperature of up to 260°C, lubricants with better high-temperature resistance are required. Conventional high-temperature resistant lubricants will fail in a short time under these environments, causing adverse effects on bearings, chains, slide rails and gears. Summary of the Invention

[0004] In response to the problems existing in the prior art, the purpose of the present invention is to provide a high-temperature resistant industrial lubricant and a preparation method thereof. By introducing special high-temperature resistant composite microcapsules into the conventional components of the lubricant, an adhesion effect can be generated on the surface of mechanical metal to form a microcapsule layer. The silicone oil wrapped inside will be slowly released to form an effective boundary lubrication film on the surface of the mechanical metal, so that the friction coefficient and wear rate of the mechanical metal surface are significantly reduced, thereby effectively reducing the heat generation during the friction process and lowering the ambient temperature of the mechanical metal. At the same time, in combination with carbon nanotubes, the lubricant has good thermal conductivity, which can further improve the high-temperature resistance.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A high-temperature resistant industrial lubricant comprises the following raw materials in parts by weight: 25-40 parts of hydrogenated base oil, 15-25 parts of synthetic base oil, 3-6 parts of high-temperature resistant composite microcapsules, 1-2 parts of carbon nanotubes, 1-2 parts of trihydroxybenzoic acid, 0.1-0.8 parts of sulfonate, 1-5 parts of surfactant, 0.5-1.0 parts of antioxidant, and 1-2 parts of dispersant.

[0007] As a further preferred embodiment of the present invention, the synthetic base oil is a poly-alpha olefin copolymer, and the poly-alpha olefin copolymer is a mixture of PAO-6, PAO-8 and PAO-10, with a mass ratio of the three being 1:1:(1-2);

[0008] The antioxidant is a mixture of an amine antioxidant and a phosphite in a mass ratio of (1-3):1;

[0009] The dispersant is at least one of triethylhexyl phosphate, methyl amyl alcohol, polyacrylamide, and fatty acid polyethylene glycol ester;

[0010] The surfactant is at least one of coconut oil diethanolamide, polyoxyethylene alkyl alcohol amide, and fatty acid polyoxyethylene ester.

[0011] As a further preferred embodiment of the present invention, the preparation method of the high temperature resistant composite microcapsules is as follows:

[0012] 1) Silicone oil and polysulfone powder are added to dichloromethane and magnetically stirred at 30-35° C. until the solution is clear to obtain an oil phase. Polyvinyl alcohol and gelatin are then placed in deionized water and magnetically stirred at 90-96° C. until the solution is clear to obtain an aqueous phase. The aqueous phase is placed in a container and mechanically stirred at 400-600 rpm and 35-38° C. During this process, the oil phase is slowly added and the reaction is continued for 3-5 hours. The obtained product is filtered, washed, and dried to obtain microcapsules;

[0013] 2) placing tris(hydroxymethyl)aminomethane in water containing dopamine hydrochloride and adjusting the pH thereof to 8-9, then dispersing the microcapsules and the composite gel in the above solution, stirring at 300-500 rpm for 12-16 hours at room temperature, filtering, washing, and drying the obtained product to obtain pretreated microcapsules;

[0014] 3) Add the pretreated microcapsules to ethanol containing ammonia water, condense and reflux at 200-300 r / min and 60-65° C., then dissolve tetraethyl silicate in ethanol and slowly add it dropwise to the above solution and continue the reaction for 24-30 hours. After filtering the obtained product, repeatedly wash it with ethanol and dry it to obtain high-temperature resistant composite microcapsules.

[0015] As a further preferred embodiment of the present invention, in the oil phase, the ratio of silicone oil, polysulfone powder, and dichloromethane is (2-5) g: (1-3) g: (30-60) mL;

[0016] In the aqueous phase, the usage ratio of polyvinyl alcohol, gelatin and deionized water is (1-3) g: (1-3) g: (100-150) mL.

[0017] As a further preferred embodiment of the present invention, the usage ratio of tris(hydroxymethyl)aminomethane, water containing dopamine hydrochloride, microcapsule, and composite gel is (0.2-0.6) g: (150-200) mL: (2-5) g: (0.8-2.0) g;

[0018] In the water containing dopamine hydrochloride, the content of dopamine hydrochloride is (0.2-0.5) g / (150-200) mL.

[0019] As a further preferred embodiment of the present invention, the ratio of the amount of the pretreated microcapsules, ethanol containing ammonia water, tetraethyl silicate, and ethanol is (1-3) g: (100-150) mL: (8-10) mL: (10-15) mL;

[0020] The content of ammonia in the ethanol containing ammonia is (10-20) mL / (100-150) mL.

[0021] As a further preferred embodiment of the present invention, the preparation method of the composite gel is as follows:

[0022] 1) dissolving an appropriate amount of aluminum isopropoxide in ethanol to prepare an aluminum isopropoxide solution, adding polyvinyl pyrrolidone to the aluminum isopropoxide solution, and stirring thoroughly to obtain a spinning solution. The spinning solution is subjected to electrospinning, and the obtained fibers are placed in a muffle furnace, and calcined at 900-960° C. and 1200-1250° C. for 10-15 hours at a heating rate of 5-8° C. / min, respectively, and naturally cooled to room temperature to obtain nanofibers;

[0023] 2) Aluminum sec-butoxide is added to deionized water at 80-85° C. and stirred at a constant temperature of 300-500 r / min for 5-10 minutes. Then, an appropriate amount of dilute nitric acid is added and stirred for 30-40 minutes to obtain a translucent aluminum sol with a slightly sky blue color. Then, under constant stirring, the silica sol is slowly added to the aluminum sol according to a molar ratio of aluminum: silicon of (2-5):1. Then, nanofibers are added and stirred thoroughly to obtain a mixed sol. After standing at a constant temperature of 80-85° C. for 5-8 hours, the mixed sol is freeze-dried and heat-treated at 450-480° C. and 950-1000° C. in a muffle furnace for 5-10 hours to obtain a composite gel.

[0024] As a further preferred embodiment of the present invention, the concentration of the aluminum isopropoxide solution is 2.5-4.5 wt %;

[0025] In the spinning solution, the content of polyvinyl pyrrolidone is 10-15wt%;

[0026] In the electrospinning, the voltage is 15-18 kV and the propulsion speed is 1.0-1.5 mL / h.

[0027] As a further preferred embodiment of the present invention, the concentration of the dilute nitric acid is 1-2 mol / L;

[0028] The added amount of the nanofiber is 2-6% of the mass of the aluminum sol.

[0029] A method for preparing high-temperature resistant industrial lubricating oil specifically comprises the following steps:

[0030] 1) Weighing each component according to the formula, stirring and mixing the high-temperature resistant composite microcapsules, carbon nanotubes, and surfactant to prepare a mixture A, which is set aside;

[0031] 2) The remaining components are stirred and mixed to obtain a mixture B, and then the mixture A and the mixture B are stirred and mixed to obtain the desired high-temperature resistant industrial lubricant.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] In the present invention, a solvent volatilization method is used to prepare microcapsules with controllable wall thickness, core material content and particle size, and then the surface of the microcapsule is functionalized by the oxidative self-polymerization of dopamine, and a composite gel is added to wrap the surface of the microcapsule to form a gel layer, and finally a layer of silica shell is deposited on the surface of the functionalized microcapsule by a sol-gel method in the form of secondary wall building, thereby forming a high-temperature resistant composite microcapsule with a double-wall structure and high thermal stability. The silica nanoparticles deposited on the surface of the high-temperature resistant composite microcapsule completely wrap the surface of the microcapsule wall material inside the silica layer, which has a good protective effect on the wall material, making the wall material of the microcapsule not easy to decompose under high temperature environment, thereby It can effectively improve the high-temperature resistance of lubricating oil, so that the lubricating oil will not fail in a high-temperature environment; and, after the high-temperature resistant composite microcapsules are treated with dopamine, the unique functional groups of polydopamine enable it to produce an adhesion effect on the surface of mechanical metal, forming a microcapsule layer. During the operation of the machine, the friction effect causes some of the high-temperature resistant composite microcapsules to rupture, and the silicone oil wrapped inside will be slowly released, thereby forming an effective boundary lubrication film on the surface of the mechanical metal, which significantly reduces the friction coefficient and wear rate of the mechanical metal surface. On the one hand, it can reduce the heat generation during the friction process, and at the same time reduce the deformation degree of the mechanical metal surface and reduce the damage to the mechanical metal, thereby helping to improve the service life of the mechanical metal.

[0034] The prepared composite gel is introduced into a high-temperature resistant composite microcapsule to form a gel layer between the double walls of the high-temperature resistant composite microcapsule. The composite gel is compounded with silicon dioxide and aluminum oxide by a sol-gel method of a co-prepolymer, and nanofibers are introduced, and the composite gel is obtained by vacuum freeze-drying. The introduced nanofibers are cross-linked with each other in the gel structure to form a network structure. On the one hand, the cross-linking degree of the network structure in the gel structure can be increased, so that the formed composite gel can better prevent convective heat transfer and heat conduction, thereby having an extremely low thermal conductivity coefficient. On the other hand, the network structure formed by the cross-linking of the nanofibers plays a supporting role, which can prevent the composite gel from being damaged in subsequent high-temperature heat treatment. The collapse of the pore structure occurs, thereby avoiding the reduction of the specific surface area of ​​the composite gel. Due to the porous structure and large specific surface area of ​​the composite gel, it has an ultra-low density. Introducing it into the high-temperature resistant composite microcapsule will not have a substantial impact on its weight, so it will not cause the high-temperature resistant composite microcapsule to settle in the lubricating oil. Moreover, the formation of the gel layer can further protect the wall material, prevent the entry of heat, and make the wall material have a better decomposition temperature, thereby further improving the high-temperature resistance of the high-temperature resistant composite microcapsule and better protecting the wall material, thereby improving the stability of the high-temperature resistant composite microcapsule in a high-temperature environment.

[0035] In the present invention, by introducing specially prepared high-temperature resistant composite microcapsules into the conventional components of lubricating oil, an adhesion effect can be generated on the surface of mechanical metal to form a microcapsule layer. The silicone oil wrapped inside will be slowly released to form an effective boundary lubrication film on the surface of the mechanical metal, so that the friction coefficient and wear rate of the mechanical metal surface are significantly reduced, thereby effectively reducing the heat generation during the friction process and lowering the ambient temperature of the mechanical metal. At the same time, in combination with carbon nanotubes, the lubricating oil has good thermal conductivity, which can further improve the high-temperature resistance. DETAILED DESCRIPTION

[0036] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0037] In an embodiment of the present invention, the synthetic base oil is a polyalphaolefin copolymer, which is a mixture of PAO-6, PAO-8, and PAO-10 in a mass ratio of 1:1:2; the antioxidant is a mixture of an amine antioxidant and a phosphite in a mass ratio of 2:1; the dispersant is triethylhexyl phosphoric acid; and the surfactant is coconut diethanolamide.

[0038] Example 1

[0039] A high-temperature resistant industrial lubricant, comprising the following raw materials in parts by weight: 25 parts of hydrogenated base oil, 15 parts of synthetic base oil, 3 parts of high-temperature resistant composite microcapsules, 1 part of carbon nanotubes, 1 part of trihydroxybenzoic acid, 0.1 part of sulfonate, 1 part of surfactant, 0.5 part of antioxidant, and 1 part of dispersant;

[0040] The preparation method of the high-temperature resistant industrial lubricant is as follows:

[0041] 1) Weighing each component according to the formula, stirring and mixing the high-temperature resistant composite microcapsules, carbon nanotubes, and surfactant to prepare a mixture A, which is set aside;

[0042] 2) The remaining components are stirred and mixed to obtain a mixture B, and then the mixture A and the mixture B are stirred and mixed to obtain the desired high-temperature resistant industrial lubricant.

[0043] The preparation method of the high temperature resistant composite microcapsules is as follows:

[0044] 1) dissolving an appropriate amount of aluminum isopropoxide in ethanol to prepare an aluminum isopropoxide solution with a concentration of 2.5 wt %, adding polyvinyl pyrrolidone to the aluminum isopropoxide solution, and stirring thoroughly to obtain a spinning solution, wherein the polyvinyl pyrrolidone content in the spinning solution is controlled to be 10 wt %, and electrospinning the spinning solution at a voltage of 15 kV and a propulsion speed of 1 mL / h. The obtained fibers are placed in a muffle furnace and calcined at 900° C. and 1200° C. for 10 h, respectively, at a heating rate of 5° C. / min, and then naturally cooled to room temperature to obtain nanofibers;

[0045] 2) Aluminum sec-butoxide was added to 80°C deionized water, stirred at a constant temperature of 300 r / min for 5 minutes, and then an appropriate amount of 1 mol / L dilute nitric acid was added and stirred for 30 minutes to obtain a translucent slightly sky blue aluminum sol. Then, under constant stirring, the silica sol was slowly added to the aluminum sol at a molar ratio of aluminum to silicon of 2:1, and then nanofibers were added and stirred thoroughly to obtain a mixed sol. The amount of nanofiber added was controlled to be 2% of the mass of the aluminum sol. After being allowed to stand at a constant temperature of 80°C for 5 hours, the mixture was freeze-dried and heat-treated at 450°C and 950°C in a muffle furnace for 5 hours, respectively, to obtain a composite gel.

[0046] 3) 2 g of silicone oil and 1 g of polysulfone powder were added to 30 mL of dichloromethane and magnetically stirred at 30°C until the solution became clear to obtain an oil phase. 1 g of polyvinyl alcohol and 1 g of gelatin were then placed in 100 mL of deionized water and magnetically stirred at 90°C until the solution became clear to obtain an aqueous phase. The aqueous phase was placed in a container and mechanically stirred at 400 rpm and 35°C. During this process, the oil phase was slowly added and the reaction was continued for 3 h. The obtained product was filtered, washed, and dried to obtain microcapsules.

[0047] 4) 0.2 g of tris(hydroxymethyl)aminomethane was placed in 150 mL of water containing 0.2 g of dopamine hydrochloride and the pH was adjusted to 8. 2 g of microcapsules and 0.8 g of the composite gel were dispersed in the solution and stirred at 300 rpm for 12 h at room temperature. The obtained product was filtered, washed, and dried to obtain pretreated microcapsules;

[0048] 5) 1 g of pretreated microcapsules was added to 100 mL of ethanol containing 10 mL of ammonia water, and the mixture was refluxed at 200 r / min and 60°C. 8 mL of tetraethyl silicate was dissolved in 10 mL of ethanol and slowly added dropwise to the above solution. The reaction was continued for 24 h. The obtained product was filtered, repeatedly washed with ethanol, and then dried to obtain high-temperature resistant composite microcapsules.

[0049] Example 2

[0050] A high-temperature resistant industrial lubricant, comprising the following raw materials in parts by weight: 30 parts of hydrogenated base oil, 20 parts of synthetic base oil, 5 parts of high-temperature resistant composite microcapsules, 2 parts of carbon nanotubes, 1.5 parts of trihydroxybenzoic acid, 0.5 parts of sulfonate, 3 parts of surfactant, 0.7 parts of antioxidant, and 1.5 parts of dispersant;

[0051] The preparation method of the high-temperature resistant industrial lubricant is as follows:

[0052] 1) Weighing each component according to the formula, stirring and mixing the high-temperature resistant composite microcapsules, carbon nanotubes, and surfactant to prepare a mixture A, which is set aside;

[0053] 2) The remaining components are stirred and mixed to obtain a mixture B, and then the mixture A and the mixture B are stirred and mixed to obtain the desired high-temperature resistant industrial lubricant.

[0054] The preparation method of the high temperature resistant composite microcapsules is as follows:

[0055] 1) dissolving an appropriate amount of aluminum isopropoxide in ethanol to prepare an aluminum isopropoxide solution with a concentration of 3 wt %, adding polyvinyl pyrrolidone to the aluminum isopropoxide solution, and stirring thoroughly to obtain a spinning solution, wherein the polyvinyl pyrrolidone content in the spinning solution is controlled to be 12 wt %, and electrospinning the spinning solution at a voltage of 16 kV and a propulsion speed of 1.2 mL / h. The obtained fibers are placed in a muffle furnace and calcined at 950° C. and 1230° C. for 12 h, respectively, at a heating rate of 6° C. / min, and then naturally cooled to room temperature to obtain nanofibers;

[0056] 2) Aluminum sec-butoxide was added to 82°C deionized water, stirred at a constant temperature of 400 rpm for 7 minutes, and then an appropriate amount of 1.5 mol / L dilute nitric acid was added and stirred for 35 minutes to obtain a translucent slightly sky-blue aluminum sol. Then, under constant stirring, the silica sol was slowly added to the aluminum sol at a molar ratio of aluminum to silicon of 3:1, and then nanofibers were added and stirred thoroughly to obtain a mixed sol. The amount of nanofiber added was controlled to be 5% of the mass of the aluminum sol. After being kept at a constant temperature of 82°C for 7 hours, the mixture was freeze-dried and heat-treated at 460°C and 980°C in a muffle furnace for 7 hours respectively to obtain a composite gel.

[0057] 3) Add 3 g of silicone oil and 2 g of polysulfone powder to 50 mL of dichloromethane and magnetically stir at 32°C until the solution is clear to obtain an oil phase. Then, place 2 g of polyvinyl alcohol and 2 g of gelatin in 120 mL of deionized water and magnetically stir at 95°C until the solution is clear to obtain an aqueous phase. The aqueous phase is placed in a container and mechanically stirred at 500 rpm and 36°C. During this process, the oil phase is slowly added and the reaction is continued for 4 hours. The obtained product is filtered, washed, and dried to obtain microcapsules.

[0058] 4) 0.5 g of tris(hydroxymethyl)aminomethane was placed in 180 mL of water containing 0.3 g of dopamine hydrochloride and the pH was adjusted to 8.5. 3 g of microcapsules and 1.5 g of the composite gel were dispersed in the solution and stirred at 400 rpm for 15 h at room temperature. The obtained product was filtered, washed, and dried to obtain pretreated microcapsules;

[0059] 5) Add 2 g of pretreated microcapsules to 120 mL of ethanol containing 15 mL of ammonia water, reflux at 250 r / min and 62°C, then slowly add 9 mL of tetraethyl silicate dissolved in 12 mL of ethanol dropwise to the above solution and continue the reaction for 28 h. The obtained product is filtered, repeatedly washed with ethanol, and then dried to obtain high-temperature resistant composite microcapsules.

[0060] Example 3

[0061] A high-temperature resistant industrial lubricant, comprising the following raw materials in parts by weight: 40 parts of hydrogenated base oil, 25 parts of synthetic base oil, 6 parts of high-temperature resistant composite microcapsules, 2 parts of carbon nanotubes, 2 parts of trihydroxybenzoic acid, 0.8 parts of sulfonate, 5 parts of surfactant, 1.0 part of antioxidant, and 2 parts of dispersant;

[0062] The preparation method of the high-temperature resistant industrial lubricant is as follows:

[0063] 1) Weighing each component according to the formula, stirring and mixing the high-temperature resistant composite microcapsules, carbon nanotubes, and surfactant to prepare a mixture A, which is set aside;

[0064] 2) The remaining components are stirred and mixed to obtain a mixture B, and then the mixture A and the mixture B are stirred and mixed to obtain the desired high-temperature resistant industrial lubricant.

[0065] The preparation method of the high temperature resistant composite microcapsules is as follows:

[0066] 1) dissolving an appropriate amount of aluminum isopropoxide in ethanol to prepare an aluminum isopropoxide solution with a concentration of 4.5 wt %, adding polyvinyl pyrrolidone to the aluminum isopropoxide solution, and stirring thoroughly to obtain a spinning solution, wherein the polyvinyl pyrrolidone content in the spinning solution is controlled to be 15 wt %, and electrospinning the spinning solution at a voltage of 18 kV and a propulsion speed of 1.5 mL / h. The obtained fibers are placed in a muffle furnace and calcined at 960° C. and 1250° C. for 15 h, respectively, at a heating rate of 8° C. / min, and then naturally cooled to room temperature to obtain nanofibers;

[0067] 2) Aluminum sec-butoxide was added to 85°C deionized water, stirred at a constant temperature of 500 rpm for 10 minutes, and then an appropriate amount of 2 mol / L dilute nitric acid was added and stirred for 40 minutes to obtain a translucent slightly sky-blue aluminum sol. Then, under constant stirring, the silica sol was slowly added to the aluminum sol at a molar ratio of aluminum to silicon of 5:1, and then nanofibers were added and stirred thoroughly to obtain a mixed sol. The amount of nanofiber added was controlled to be 6% of the mass of the aluminum sol. After being allowed to stand at a constant temperature of 85°C for 8 hours, the mixture was freeze-dried and heat-treated at 480°C and 1000°C in a muffle furnace for 10 hours, respectively, to obtain a composite gel.

[0068] 3) 5 g of silicone oil and 3 g of polysulfone powder were added to 60 mL of dichloromethane and magnetically stirred at 35°C until the solution was clear to obtain an oil phase. 3 g of polyvinyl alcohol and 3 g of gelatin were then placed in 150 mL of deionized water and magnetically stirred at 96°C until the solution was clear to obtain an aqueous phase. The aqueous phase was placed in a container and mechanically stirred at 600 rpm and 38°C. During this process, the oil phase was slowly added and the reaction was continued for 5 h. The obtained product was filtered, washed, and dried to obtain microcapsules.

[0069] 4) 0.6 g of tris(hydroxymethyl)aminomethane was placed in 200 mL of water containing 0.5 g of dopamine hydrochloride and the pH was adjusted to 9. 5 g of microcapsules and 2.0 g of the composite gel were dispersed in the solution and stirred at 500 rpm for 16 h at room temperature. The obtained product was filtered, washed, and dried to obtain pretreated microcapsules;

[0070] 5) Add 3 g of pretreated microcapsules to 150 mL of ethanol containing 20 mL of ammonia water, reflux at 300 r / min and 65°C, then slowly add 10 mL of tetraethyl silicate dissolved in 15 mL of ethanol dropwise to the above solution and continue the reaction for 30 h. The obtained product is filtered, repeatedly washed with ethanol, and then dried to obtain high-temperature resistant composite microcapsules.

[0071] Comparative Example 1: This comparative example is basically the same as Example 1, except that it does not contain high-temperature resistant composite microcapsules.

[0072] Comparative Example 2: This comparative example is basically the same as Example 1, except that nanofibers are not included in the preparation process of the high-temperature resistant composite microcapsules.

[0073] Comparative Example 3: This comparative example is basically the same as Example 1, except that no composite gel is contained during the preparation of the high-temperature resistant composite microcapsules.

[0074] Comparative Example 4: This comparative example is basically the same as Example 1, except that step 4) is omitted during the preparation of the high-temperature resistant composite microcapsules.

[0075] Comparative Example 5: This comparative example is basically the same as Example 1, except that step 5) is omitted during the preparation of the high-temperature resistant composite microcapsules.

[0076] Test Experiment

[0077] 1) Anti-wear and wear resistance of each group of lubricants: A four-ball testing machine was used to evaluate the anti-wear performance of the lubricants at 25°C. The maximum no-stick load (PB) was determined according to the national standard GB3142. After the test, the wear spot diameter was measured, and the anti-wear and wear reduction performance values ​​were measured using a micro-vibration tribometer. The results are shown in Table 1.

[0078] Table 1

[0079]

[0080] As can be seen from Table 1, the high-temperature resistant industrial lubricant of the present invention has stable components, low volatility, good safety, and greatly reduces the friction coefficient, thereby reducing power loss, small temperature rise, and has good wear resistance and high temperature resistance.

[0081] 2) The high temperature resistance and kinematic viscosity of each group of lubricating oils were measured. The high temperature resistance was measured by measuring the decomposition temperature of the lubricating oils, and the kinematic viscosity was measured according to the national standard GB / T265. The measurement results are shown in Table 2.

[0082] Table 2

[0083]

[0084]

[0085] As shown in Table 2, the high temperature resistant industrial lubricant of the present invention has a decomposition temperature of up to 485°C, has significant high temperature resistance, and maintains a kinematic viscosity of 12.41-12.83 mm 2 / s, with good viscosity.

[0086] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to the specific embodiments described. Obviously, many modifications and variations are possible based on the content of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A high temperature resistant industrial lubricant, characterized in that: The raw materials include the following parts by weight: 25-40 parts of hydrogenated base oil, 15-25 parts of synthetic base oil, 3-6 parts of high temperature resistant composite microcapsules, 1-2 parts of carbon nanotubes, 1-2 parts of trihydroxybenzoic acid, 0.1-0.8 parts of sulfonate, 1-5 parts of surfactant, 0.5-1.0 parts of antioxidant, and 1-2 parts of dispersant; The synthetic base oil is a poly-alpha-olefin copolymer, and the poly-alpha-olefin copolymer is a mixture of PAO-6, PAO-8 and PAO-10, and the mass ratio of the three is 1:1:(1-2); The antioxidant is a mixture of an amine antioxidant and a phosphite in a mass ratio of (1-3):1; The dispersant is at least one of triethylhexyl phosphoric acid, methylpentyl alcohol, polyacrylamide, and fatty acid polyethylene glycol ester; The surfactant is at least one of coconut oil diethanolamide, polyoxyethylene alkyl alcohol amide, and fatty acid polyoxyethylene ester; The preparation method of the high temperature resistant composite microcapsule is as follows: 1) Add silicone oil and polysulfone powder to dichloromethane, and stir magnetically at 30-35° C. until the solution is clear to obtain an oil phase, then place polyvinyl alcohol and gelatin in deionized water, and stir magnetically at 90-96° C. until the solution is clear to obtain an aqueous phase, place the aqueous phase in a container, and stir mechanically at 400-600 r / min and 35-38° C., slowly add the oil phase during this process, and continue the reaction for 3-5 hours, filter the obtained product, wash it, and then dry it to obtain microcapsules; 2) placing tris(hydroxymethyl)aminomethane in water containing dopamine hydrochloride and adjusting the pH thereof to 8-9, dispersing microcapsules and composite gel in the above solution, stirring at 300-500 r / min for 12-16 h at room temperature, filtering, washing and drying the obtained product to obtain pretreated microcapsules; 3) Add the pretreated microcapsules to ethanol containing ammonia water, condense and reflux at 200-300 r / min and 60-65° C., then dissolve tetraethyl silicate in ethanol and slowly add it dropwise to the above solution to continue the reaction for 24-30 hours, filter the obtained product, repeatedly wash it with ethanol and dry it to obtain high temperature resistant composite microcapsules.

2. A high temperature resistant industrial lubricating oil according to claim 1, characterized in that: In the oil phase, the ratio of silicone oil, polysulfone powder and dichloromethane is (2-5) g: (1-3) g: (30-60) mL; In the aqueous phase, the usage ratio of polyvinyl alcohol, gelatin and deionized water is (1-3) g: (1-3) g: (100-150) mL.

3. A high temperature resistant industrial lubricating oil according to claim 1, characterized in that: The usage ratio of the tris(hydroxymethyl)aminomethane, water containing dopamine hydrochloride, microcapsule and composite gel is (0.2-0.6) g: (150-200) mL: (2-5) g: (0.8-2.0) g; The content of dopamine hydrochloride in the water containing dopamine hydrochloride is (0.2-0.5) g / (150-200) mL.

4. A high temperature resistant industrial lubricating oil according to claim 1, characterized in that: The ratio of the pre-treated microcapsules, ethanol containing ammonia water, tetraethyl silicate, and ethanol is (1-3) g: (100-150) mL: (8-10) mL: (10-15) mL; The content of ammonia in the ethanol containing ammonia is (10-20) mL / (100-150) mL.

5. A high temperature resistant industrial lubricating oil according to claim 1, characterized in that: The preparation method of the composite gel is as follows: 1) dissolving an appropriate amount of aluminum isopropoxide in ethanol to prepare an aluminum isopropoxide solution, adding polyvinyl pyrrolidone to the aluminum isopropoxide solution, stirring thoroughly to obtain a spinning solution, electrospinning the spinning solution, placing the obtained fiber in a muffle furnace, calcining at 900-960° C. and 1200-1250° C. for 10-15 hours at a heating rate of 5-8° C. / min, and naturally cooling to room temperature to obtain nanofibers; 2) Aluminum 2-butoxide is added to 80-85° C. deionized water, stirred at a constant temperature of 300-500 r / min for 5-10 min, and then an appropriate amount of dilute nitric acid is added and stirred for 30-40 min to obtain a translucent slightly sky blue aluminum sol, and then under constant stirring, the silica sol is slowly added to the aluminum sol according to a molar ratio of aluminum: silicon of (2-5):1, and then the nanofibers are added and stirred thoroughly to obtain a mixed sol, which is allowed to stand at a constant temperature of 80-85° C. for 5-8 h, then freeze-dried, and heat-treated at 450-480° C. and 950-1000° C. in a muffle furnace for 5-10 h, respectively, to obtain a composite gel.

6. A high temperature resistant industrial lubricating oil according to claim 5, characterized in that: The concentration of the aluminum isopropoxide solution is 2.5-4.5wt%; In the spinning solution, the content of polyvinyl pyrrolidone is 10-15wt%; In the electrospinning, the voltage is 15-18 kV and the propulsion speed is 1.0-1.5 mL / h.

7. A high temperature resistant industrial lubricating oil according to claim 5, characterized in that: The concentration of the dilute nitric acid is 1-2 mol / L; The added amount of the nanofiber is 2-6% of the mass of the aluminum sol.

8. The method for preparing a high temperature resistant industrial lubricating oil according to any one of claims 1 to 7, characterized in that: The specific steps include: 1) Weighing each component according to the formula amount, stirring and mixing the high temperature resistant composite microcapsules, carbon nanotubes and surfactant to prepare a mixture A for standby use; 2) The remaining components are stirred and mixed to obtain a mixture B, and then the mixture A and the mixture B are stirred and mixed to obtain the desired high temperature resistant industrial lubricating oil.